Performance matching between the surface structure of cucumber powdery mildew in different growth stages and the properties of surfactant solution. Issue 7 (11th May 2021) - He, Lifei; Ding, Lei; Waterhouse, Geoffrey I N; Li, Beixing; Liu, Feng; Li, Peiqiang
Abstract: BACKGROUND: Understanding performance matching of pesticide droplets on the surface of cucumber leaves modified by powdery mildew is of practical importance for the agricultural sector. Here, the surface texture and wettability of cucumber leaves covered by powdery mildew were systematically examined using parameters such as micromorphology, physicochemical properties, and liquid droplet contact angle measurements. RESULTS: Our results show that powdery mildew growth can be divided into four distinct stages according to the surface texture characteristics of the diseased cucumber leaves. The three‐dimensional (3D) surface structures of powdery mildew layers on cucumber leaves had individual characteristics at different mildew growth stages, among which powdery mildew was more easily spread in the last growth stage, and powdery mildew height was greatest in the NO. 2 growth stage ( S a  = 425.35 μm). Surface free energy values, static contact angle, and contact angle hysteresis all correlated strongly with the surface characteristics of powdery mildew layers at different growth stages. When the concentration of surfactant reached the critical micelle concentration, the wetting state of AEO‐5 solution droplets on the surface of cucumber powdery mildew leaves reached the Wenzel state more easily. The wettability of a droplet on the leaf surface depends on the state of the monomer and micelle in the surfactant solution and the surface characteristics of the powdery mildew‐covered leaf. CONCLUSION: The 3D structure and relative dielectric constant of powdery mildew‐covered leaves influenced surface texture characteristics, which in turn controlled the wetting and matching ability of surfactant droplets on diseased leaves. This work provides valuable new insights into the matching of the structure of powdery mildew‐covered plant leaves with the properties of surfactant solutions. © 2021 Society of Chemical Industry. Abstract : © 2021 Society of Chemical Industry.